Signalling networks, inflammation and innate immunity. (1st December 2003) - Dower, S.K.; Qwarnstrom, E.E.
Abstract : We have been analysing the signalling systems that couple to receptors of the TIR (Toll/interleukin-1 receptor) family, which signal through a common cytoplasm region; the TIR domain. These systems are of both practical and fundamental biological significance, being central to the pathogenesis of chronic inflammatory diseases such as atherosclerosis, to host defence throughout the biological world, and are ancient in the context of life on earth, having originated more than 1 billion years ago: prior to the divergence of plants and animals. TIR domain receptors couple to at least two sets of well-characterized pathways: those leading to the activation of inhibitory κB kinase complexes/nuclear factor κB, and those leading to the activation of mitogen-activated protein kinase/AP-1/ATF-2 etc. We have been investigating these systems using a combination of expression screening methods to identify new components, and real-time green fluorescent protein-based techniques to observe execution of signalling programmes in real time. Our data reveal that there is a very large level of cell-to-cell variation in signal programme execution even in clonal populations and that at least one mechanism for dealing with this heterogeneity is the assembly of signal transduction components into large multiprotein complexes.